THE UNIQUENESS OF THE BARIS MEMEDI DANCE IN THE TRADITIONAL VILLAGE OF JATILUWIH, TABANAN, BALI - Putra, Komang Dedy Kurniawan; Permanamiarta, Putu Agus; Laksana, I Made Darma (Stilistika : Jurnal Pendidikan Bahasa dan Seni, 2024)
Baris Memedi Dance is a sacred dance performed as part of the ritual infrastructure during the mass cremation ceremony (Ngaben Massal) in the Jatiluwih Traditional Village. The main issue addressed in this journal is the uniqueness exclusive to the Baris Memedi Dance. Therefore, the objective of this research is to explore and gain a deeper understanding of the uniqueness and distinctive characteristics found only in the Baris Memedi Dance in the Jatiluwih Traditional Village. The research type employed in this journal is qualitative research, with the data collection method being literature review. Based on the method used, the data revealed uniqueness in costume, makeup, and dance style. The distinctive feature of the Baris Memedi Dance is that it must be performed in an odd number, using costumes resembling dried leaves, dried banana leaves, or rice plant, creating the appearance of supernatural beings (Memedi). The dancers also use fabrics from graves, and their faces are painted with charcoal from graves to resemble Memedi (supernatural beings). The Baris Memedi dancers are adorned in a way that gives them a frightening appearance. Baris Memedi dancers can perform in a conscious state or semi-conscious state, but they remain in control.